Cost Assessment of Initial Radiological Modalities for Evaluation of Adult Patient with Asymptomatic Microscopic Hematuria at Thammasat University Hospital - Tangtiang, Kaan; Laopiyatassanee, Gritsana; Lohitvisate, Wanrudee; Tangpaitoon, Teerayut (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Asymptomatic Microscopic Hematuria (AMH) is highly prevalent. There is controversy regarding the radiologic evaluation in the patient with AMH. The choice of diagnostic evaluation for patient with AMH has broad clinical and economic implication. As of now, no study aims to determine worthiness of each radiologic evaluation. Objective: To estimate the capability and cost per positive unit for abnormality detection of 5 radiologic evaluations in patient with AMH. Methods: The detection rate of four diagnostic approaches (Plain KUB radiography, intravenous pyelography (IVP), ultrasound (US) and, unenhanced computed tomography) were evaluated and compared to the reference enhance computed tomography (CT). Cost per positive unit was determined by number of abnormality detection in all 5 radiological evaluations. Results: The KUB US has highest detection rate (51.2%). When comparing others radiologic evaluation with enhanced CT, there is no significant difference on their performance in lesion detection. In male patients, US has least cost per positive unit (1,050 Bahts) and highest detection rate (66.7%). While plain KUB radiography has least cost per positive unit (440 Bahts) in female patients with detection rate between plain KUB radiography and US are very close (28.3% to 37.8%). Conclusions: IVP is not a suitable initial investigation for AMH, according to its low detection rate and high cost per positive unit. US is the most useful tool in KUB abnormality detection. Plain KUB radiography has the lowest cost per positive unit in our study.